The search party - Richell, Hannah (Atria Books, an imprint of Simon & Schuster, Inc., 2024)
"A group of college friends reunite with their families on a glamping weekend in Cornwall when a powerful storm leaves them stranded, forcing them to confront long-held secrets and a dangerous disappearance"--